Association Between Sleep Traits and Rheumatoid Arthritis: A Mendelian Randomization Study - Gao, Rui-Chen; Sang, Ni; Jia, Cheng-Zhen; Zhang, Meng-Yao; Li, Bo-Han; Wei, Meng; Wu, Guo-Cui (Frontiers in Public Health, 2022)
Currently, the causal association between sleep disorders and rheumatoid arthritis (RA) has been poorly understood. In this two-sample Mendelian randomization (TSMR) study, we tried to explore whether sleep disorders are causally associated with RA. Seven sleep-related traits were chosen from the published Genome-Wide Association Study (GWAS): short sleep duration, frequent insomnia, any insomnia, sleep duration, getting up, morningness (early-to-bed/up habit), and snoring, 27, 53, 57, 57, 70, 274, and 42 individual single-nucleotide polymorphisms (SNPs) (P<5×10-8) were obtained as instrumental variables (IVs) for these sleep-related traits. Outcome variables were obtained from a public GWAS study that included 14,361 cases and 43,923 European Ancestry controls. The causal relationship between sleep disturbances and RA risk were evaluated by a two-sample Mendelian randomization (MR) analysis using inverse variance weighted (IVW), MR-Egger regression, weighted median, and weight mode methods. MR-Egger Regression and Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) were used to test for horizontal pleomorphism and outliers. There was no evidence of a link between RA and frequent insomnia (IVW, odds ratio (OR) : 0.99; 95% interval (CI): 0.84 -1.16; P = 0.858), any insomnia (IVW, OR: 1.09; 95% CI: 0.85 - 1.42; P = 0.489), sleep duration (IVW, OR: 0.65, 95% CI: 0.38-1.10, P = 0.269), getting up (IVW, OR: 0.56, 95% CI: 0.13-2.46, P = 0.442), morningness (IVW, OR: 2.59; 95% CI: 0.73-9.16; P = 0.142), or snoring (IVW, OR: 0.95; 95% CI: 0.68-1.33; P = 0.757). Short sleep duration (6h) had a causal effect on RA, as supported by IVW and weighted median (OR:1.47, 95% CI: 1.12–1.94, P = 0.006; OR: 1.43, 95%CI:1.01-2.05, P = 0.047). Sensitivity analysis showed that the results were stable. Our findings imply that short sleep duration is causally linked to an increased risk of RA. Therefore, sleep length should be considered in disease models, and physicians should advise people to avoid short sleep duration practices to lower the risk of RA.